Study of harmonic distortion from variable speed drive and energy saving lamps - Yulianta Siregar; Waleed Khalid Al-Azzawi; Zulkarnaen Pane; Unedo E Parhusip; Suherman Suherman (Institute of Advanced Engineering and Science, 2022)
The power electronic component has been widely used in the current industrial era. It has been considered more efficient than the previous devices as it saves more space and uses less power. One example of power electronic components is the variable speed drive for speed regulation of electric motors in the industrial world. Another application of power electronic components is to be used in energy-saving lamps. The use of power electronic components in these two loads generates harmonic distortion and reduces network power quality. In this paper, the authors analyzed the harmonics in both loads. As a result, the total harmonic distortion (THD) current for four energy-saving lamps is 88.3%. Meanwhile, the THD current at the 50 Hz, 5 A, and variable speed drive is 46.2%. After mixing the two loads, the THD current decreases by around 35%.